Pendidikan Multikultural dalam Sistem Pendidikan Indonesia: Konsep, Tantangan, dan Peran Guru dalam Membangun Toleransi, Keadilan, dan Kesetaraan - Deswina Putri; Rizky Faridah; Muthmainnah Muthmainnah; Muhammad Yasin (Yayasan Miftahul Ulum Sangatta Kutai Timur (KEP. MENKUMHAM RI No. AHU-0014779.AH.01.04.Tahun 2018) bekerjasama dengan Jurusan Tarbiyah STAI SANGATTA Kab. Kutai Timur., 2025)
Multicultural education is an important requirement in Indonesia's education system, which is characterised by cultural, ethnic, religious and social diversity. This approach is necessary to foster tolerance, respect for differences and the ability to live harmoniously in a pluralistic society. The research questions in this study were simplified into three: how is the concept of multicultural education understood; what are the challenges faced in its implementation; and what strategies can be applied to optimise its implementation in educational institutions. This study aims to describe the concept of multicultural education, analyse the obstacles to its implementation, and offer relevant development strategies. The results of the study show that although multicultural education is of high urgency, its implementation still faces obstacles such as teacher readiness, an unintegrated curriculum, and limited facilities. Therefore, it is necessary to strengthen the competence of educators, integrate multicultural values into the curriculum, and provide school policy support so that multicultural education can run more effectively.